Quadruple Helix Collaboration in Efforts to Fulfill Human Security in Kemijen Village, Semarang City - Satwika Paramasatya; Yemima Galih Pradipta; Kevin Rendra Pratama; Desy Ramadhani (Parahyangan Center for International Studies, 2021)
Human security is very vital for humans. Initially, security was defined as freedom from war. However, over time it began to shift into a broad and collective concept of security. The United Nations established three important pillars of Human Security, namely: freedom from want, freedom from fear, and freedom to live in dignity. The implementation of compliance with Human Security is complex and not simple. This paper argues that the Triple Helix model, the position of society is neglected because they are only positioned as an object where they should also be the one who play an active role as actors. Therefore, a new breakthrough is needed in the effort to fulfill Human Security in Kemijen Village, Semarang City through the Quadruple Helix concept that involves government, business, academics and the community. This study uses a descriptive-qualitative approach by combining literature studies and interviews. The Quadruple Helix is basically a collaboration between top-down and bottom-up approaches, and this study proves that the Quadruple Helix model is utmost important, because the solutions are more well-targeted and meet the needs of the community. The Quadruple Helix model also allowed the people of Kemijen Village to be involved to become subjects through Focus Group Discussion.